Developing and investing in dynamic capabilities into business to enhance cybersecurity intelligence - Pigola, Angélica (2023)
With advances and outspread usage of information and communication technologies, cyberattacks are growing into frequent and serious impact. Advanced threats in cybersecurity are on the rise in industries such as healthcare, finance, technology, government, retail, transportation, and more. Cyberattacks also threaten the security of executives, entrepreneurs and employees or the general public with the loss of confidential information; damage to the reputation of companies; trouble in decision-making; monetary deficit; loss of reliability etc. Therefore, it is essential to move towards analyzing cybersecurity-related resources and capabilities to identify, prevent and respond to such breaches. In this dissertation, the general objective is to present a vision to reduce risks and sensitivities in the virtual environment of companies from the improvement of the decision-making process on investing in the development of dynamic capabilities for cybernetic protection. It is structured in three studies. The first study was a meta-synthesis to identify key cybersecurity capabilities across 47 case studies. The second study is an unprecedented empirical survey of 207 cybersecurity experts to confirm the influence of dynamic capabilities on building intelligence in information security. And finally, the third study, an experiment to evaluate iterative learning among 26 experienced and 83 non-experienced individuals in information security in relation to investments for dynamic capabilities development in information security. It was possible to understand the challenges that lead to delays in building capabilities that meet uncertain scenarios and improve the predictability of cyber incidents. Through a theoretical model on the dimensions that foster the development of cybersecurity capabilities, an empirical study to test the theoretical model and an experiment to analyze the effectiveness of decision-making on investments in the development of these capabilities, it is concluded that potential delays in building cybersecurity capabilities to address uncertain scenarios by improving the predictability of online incidents is directly linked to the invisibility of cyber risks and the knowledge required to understand them. However, the most positive aspect of these findings is based on the effective possibility of learning on how to invest in cybersecurity capabilities for those who wish to improve the organizational posture in information security. This dissertation brings an unprecedented contribution to the Brazilian scenario, as it allows companies to innovate their capabilities and resource management processes to enable greater cybersecurity and reduce the impacts of potential virtual attacks, with the probability of eradicating vulnerabilities. The developed methodological approaches can also be applied to any context under appropriate adaptations.